1998
DOI: 10.1021/jf971026l
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hydrocolloid Coating and Mushroom Structure

Abstract: Agaricus bisporus edible mushrooms were coated with different gum-based coatings, including alginate and alginate−ergosterol, with or without emulsifier. The structures of the different parts of the mushroom tissue were studied by SEM. Various penetration modes of coating and cross-linking solutions into the tissue were examined. The techniques of ICP and X-ray analysis were used to quantify the presence and depth of penetration of minerals into the mushroom tissue before and after coating. Critical surface te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 31 publications
(39 reference statements)
4
25
0
Order By: Relevance
“…Adding calcium salts to soy-protein coatings may control darkening of fruits and vegetables [Park et al, 2001]. A previous report showed that alginate-based coating solution, a carbohydrate having a carboxylic group, was effective in maintaining the better appearance and color of the mushroom for a long period [Hershko and Nussinovitch, 1998]. …”
Section: Resultsmentioning
confidence: 99%
“…Adding calcium salts to soy-protein coatings may control darkening of fruits and vegetables [Park et al, 2001]. A previous report showed that alginate-based coating solution, a carbohydrate having a carboxylic group, was effective in maintaining the better appearance and color of the mushroom for a long period [Hershko and Nussinovitch, 1998]. …”
Section: Resultsmentioning
confidence: 99%
“…Alginate coatings are good oxygen barriers that can retard lipid oxidation in various fruits and vegetables and have been found to reduce weight loss and natural microflora counts in minimally processed carrots (Amanatidou et al 2000). Calcium alginate coatings were found to improve the quality of fruits and vegetables, such as reducing shrinkage, oxidative rancidity, moisture migration, oil absorption, and sealing in volatile flavors, improving appearance and color and reducing weight loss of fresh mushrooms in comparison with uncoated ones (Hershko and Nussinovitch 1998).…”
Section: Chitosan With Alginate and Carrageenanmentioning
confidence: 99%
“…Alginate coatings are good oxygen barriers (Conca and Yang 1993) that can retard lipid oxidation in various fruits and vegetables (Kester and Fennema 1986), and have been found to reduce weight loss and natural microflora counts in minimally processed carrots (Amanatidou and others 2000). Calciumalginate coatings were found to improve the quality of fruits and vegetables, such as reducing shrinkage, oxidative rancidity, moisture migration, oil absorption, and sealing-in volatile flavors, improving appearance and color, and reducing weight loss of fresh mushrooms in comparison with uncoated ones (Hershko and Nussinovitch 1998).…”
Section: Polysaccharide-based Coatingsmentioning
confidence: 99%